Factors Affecting Trust and Interest in Transactions by Indonesian MSME Sellers in e-Commerce - Yongki Alfa Rizi; Fitra Dharma; Yunia Amelia; Tri Joko Prasetyo (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objective: This study aims to examine the factors that influence the trust and interest in e-commerce transactions among MSME actors in Indonesia. Therefore, a study was conducted on the effect of these variables. Background of the problem: The transition of MSMEs in Indonesia to using e-commerce for carrying out their business transactions. Every year, there is an increase in the number of MSMEs converting from conventional to digital, as well as the government's contribution to assist in the transition. Novelty: The variable of interest in transacting through e-commerce is the basis for conventional businesses to switch to digital, but in other studies, no one has added a variable of trust as an intervening variable, and several other supporting variables for the interest in transacting via e-commerce. This study presents new research that provides a comprehensive view of the technology acceptance model (TAM) and how it relates to trust and interest in e-commerce transactions. Research Methods: This study uses a snowball sampling technique by employing a survey of the MSMEs in Indonesia with certain criteria. This study also uses structural equation modeling (SEM) based on partial least squares (PLS). Findings/Results: This study proves that all the variables of trust and interest in e-commerce transactions are supportive and significant, but there are two hypotheses that do not support them (H3 and H6). This shows that empirically MSMEs are not necessarily interested in using e-commerce for their business transactions. Conclusion: This study provides insight into the trust and interest in e-commerce transactions among MSME business actors. We suggest that the MSMEs should switch to using e-commerce for their transactions, to develop their businesses into digital ones.